Assessment of Automatic Thoughts in Patients with Depressive Illness at a Tertiary Hospital in Nepal - Mita Rana; Sabitri Sthapit; Vidya Deb Sharma (Journal of Nepal Medical Association, 2017)
Introduction: Cognitive functions have significant influence on psycho-social and general wellbeing. The quality, content and processing of negative thoughts initiate depressive symptoms; i.e. low mood, decreased self-worth and diminished interest in pleasurable activities. The study assessed the automatic thoughts of patients having depressive illness and evaluated and compared the changes after therapy; i.e. Psychotherapy and pharmacotherapy. Methods: Diagnosed cases of depressive illness (n=135),  according to ICD-10 and study criteria, attending the out-patient clinic of Department of Psychiatry and Mental Health, Tribhuvan University Teaching Hospital, were included. Beck Depression Inventory was used to screen level of depressive symptoms. Automatic thoughts were assessed by the Automatic Thought Questionnaire-Revised before initiating therapy and after completion of therapy for comparison.  Depressive patients received either of the three treatment procedures after randomization of the study sample into three different treatment groups; i.e. Cognitive behavior therapy, pharmacotherapy or combined therapy receiving both cognitive behavior therapy and pharmacotherapy. Results: Among the total 135 patients, 53 (39.3%) had moderate, 47 (34.8%) had severe depressive and 35 (25.9%) had mild depressive symptoms before therapeutic interventions. Negative automatic thoughts were significantly present in depressed patients and reduced after all three interventions. Negative automatic thoughts of hopelessness, anxiety and inability coping were significantly reduced after therapy. Conclusions: Automatic negative thoughts were significantly correlated with depressive disorder. Combined therapy CBT with pharmacotherapy or CBT alone was found to be more effective in modifying automatic negative thoughts than pharmacotherapy alone, ultimately reducing depressive symptoms to a significant degree. Keywords: automatic thoughts; cognitive Behavior therapy; pharmacotherapy. [PubMed]